Strategi Pemasaran Jagung Di Kecamatan Palolo Kabupaten Sigi - Azria Azria (Mitra Sains, 2019)
This research aims to determine alternative marketing strategy must be established by a corn farmer in Palolo District, of Sigi. The population in this study is a corn farmer who lives in the village and the village Kapiroe, Bobo Palolo subdistrict. Given the purpose of this study focus on determining the marketing strategy must be established by a corn farmer in the District of Palolo, then the sample is limited to only six farmers, both located in the village of Bobo and villages Kapiroe, 8 traders, 1 person head of agricultural Sigi and 1 sub-district agricultural extension Palolo, so that the total number of samples that follow FGD process is as many as 16 people. Data were obtained through: observation, interviews, focus group discussion (FGD). Data were analyzed with SWOT analysis. SWOT analysis of marketing corn, factors Strength (Strengths) either: (a) The layout of the districts Palolo located, (b) high levels of production and productivity of farming corn, (c) A large number of farmers who are farming, (d) the potential institutional farmer level and (e) Agroclimate very appropriate. The factors of existing opportunities, including: (a) The opening of the market to sell the commodity corn, (b) There is support from the Department of Agriculture Sigi, (c) The high demand and the price level of corn for export commodities, (d) Determination of corn as the leading commodity Subdistrict Palolo, and (e) the development of dry corn grain prices are likely to increase. The results of the SWOT matrix marketing of this maize set "SO Strategy", as a key strategy to get attention, which is to harness the power factor possessed for available opportunities. Based on the resulting strategy of SWOT analysis, the activities proposed to be undertaken, including: (1) Improving the institutional role of the farmer in the marketing units of corn to take advantage of the opening of the market, (2) Utilizing the support of the Department of Agriculture in maintaining productivity to meet the demand of corn.